Care for hiv/aids patients: norms and biosecurity for oral health in Colombia - Acosta de Velásquez, Blanca Lucía (Acta Bioethica, 2006)
The present article describes biosecurity universal norms for dental care, specifically those referred to care of persons with HIV/AIDS, and also it reviews laws and norms at Colombia with respect to the topic. It establishes the routine of evaluating, controlling and preventing accidents at work and infections associated with dental health practices, guaranteeing a better care and quality of life both for patients and for health personnel.